Предмет: Алгебра, автор: АлинаРо2003

1. Упростите выражение:
А) 3(x-2у)-2(3х-у); Б) (2а-3b)(a+b)-(a-b).
2) Разложите на множители многочлен:
А) 6ab-3b2; Б) ac+bc-3a-3b.

Ответы

Автор ответа: lemanhuseynli001
0
N 1.
A) 3(x - 2y) - 2(3x - y) = 3x - 6y - 6x + 2y = -3x - 4y;
Б) (2a - 3b)(a + b) - (a - b) = 2a^2 + +2ab - 3ab - 3b^2 - a + b = 2a^2 - -3b^2 - a + b - ab.

N 2.
A) 6ab - 3b2 = 6ab - 6b = 2b(3a - -3).
Б) ac + bc - 3a - 3b = c(a + b) - 3(a + +b) = (c - 3)(a + b).
Автор ответа: lemanhuseynli001
0
Лучший ответ кому?
Похожие вопросы
Предмет: Алгебра, автор: haykk185